Multimorbidity patterns of dental caries and obesity/overweight among adults: a systematic review and meta-analysis - Yu, Su-Tong; Hua, Jing-Yi; Zeng, Yu-Han; Yu, Shi-Yu; Zhang, Zi-Yu; Xiao, Wan-Shu; Li, Dan-Lin (BMC oral health, 2025)
Obesity and dental caries may share common dietary and metabolic risk factors, but their association in adults remains unclear. This systematic review and meta-analysis aim to evaluate the impact of obesity/overweight on dental caries in adults. PubMed, Web of Science, Cochrane Library, and Wiley databases were searched for relevant studies published between January 2000 and January 2025. Observational studies assessing the association between obesity/overweight and dental caries were included. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using random-effects models. Eighteen cross-sectional studies with 270,408 participants were included. The meta-analysis found no significant association between obesity/overweight and dental caries risk (OR = 1.06, 95% CI = 0.98-1.14, P < 0.001). Subgroup analyses showed no significant differences based on BMI classification or geographical region. However, studies that did not adjust for confounders reported a positive association (OR = 1.17, 95% CI = 1.04-1.29, P = 0.036), which disappeared after adjusting for confounders (OR = 1.00, 95% CI = 0.89-1.12, P < 0.001). Obesity/overweight was not significantly associated with dental caries in adults, suggesting that previously observed relationships may be influenced by shared risk factors such as dietary habits, age and socioeconomic status. Future studies should pay attention to potential confounders and adopting prospective cohort designs or Mendelian randomization approaches may help explore causual relationshhips.